Media Independent Interface (MII) implementation and data processing on FPGA for Fast ETHERNET transmission over Plastic Optical Fiber - Ramírez-Molina, Julio César (Instituto Tecnológico de Costa Rica, 2008)
This thesis focuses on the design and implementation of a Media Converter, which allows Ethernet Communication through 250 meters of Plastic Optical Fiber (POF). Three subsystems constitute this system. First, a configurable MII Interface which provides Full Duplex Communication through the Ethernet at different data rates (10Mpbs and 100Mbps). The User defines the data rate according to the capabilities of his Modulator. The second subsystem is the Transmission Module. This module receives Ethernet data provided by the MII interface in order to encode it. Then it generates a Reed Solomon verifying sequence used by the receiver to correct the frame errors and to certificate the frame accuracy. Finally, the third subsystem is a Testing Unit. It is used in the development and debugging process of the prototype. This module emulates a real data transmission using a Pseudo Random Bit sequence (PRBS). The data received is stored and then downloaded by a block called Downloading Unit that executes Direct Memory Access (DMA) transfers between the memory of the Testing Unit and a computer. The transfers are made through the USB port of the PC.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2008
Keywords: Hardware; Software; USB; Diseño; Fibra óptica